Analisis Berth Occupancy Ratio (BOR) Untuk Memenuhi Standar Ultilitas Dirjen Perhubungan laut Pada Dermaga B Curah Cair Pelabuhan Dumai - Doris Ade Widyarti; Rinaldi Rinaldi; Ferry Fatnanta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Berth B (The pour liquid berth) is one of the berth which has a higher activity in Dumai Harbour. Berth B handling cargo activities dominated by CPO with the amount up to 5 million tons each year and come increasing every year. The increasing amount of CPO, need a project to know the value of visiting ships and the value of BOR in short term. Project value is required to evaluate performance of the port so in the future the berth still being capable to manage activities of cargo handling. Based on results of analysis, the value of BOR in short time projection until 2021 is 82.90%. To fulfill The Standard Of Managing Director Of Marine in 2011, the value of BOR was 70% it could be did by adding the lenghth of berth and increase discharge of the pump. The short time projection in 2021 the Berth should be lengthnened formerly 800 meters become 961 meters. Another solution that could be done without adding the length of berth is increased the discharge of pump. The capacity of pump formerly 200 tons/hour, by increased the discharge into 250 ton/hour the value of a BOR become 62.18%Keywords: harbour, berth, cargo handling of CPO, BOR, projection